Representation of the History of the Technical Progress in the Literature about Economic Growth: A Comment - SAMET, Kaies (Asian Development Policy Review, 2018)
The aim of this paper is to analyse the history of the technological change, more specifically the technical progress, in related literature and its impact on the economic growth. A set of theories have been historically developed from the Schumpeterian theory till the new growth theories as the 1980’s endogenous growth theory and the 1990’s neo-Schumpeterian endogenous growth theory. Thanks to their ideas, these last theories have known growing interest among economists, exceeding, therefore, the Schumpeterian theory.